KONSELING BEHAVIORISTIK DENGAN TEKNIK BEHAVIOR CONTRACT UNTUK MENINGKATKAN LITERASI MEMBACA PADA SISWA MTS SABILUL ULUM - Amalia, Khusnu; Hidayati, Richma; Kiswantoro, Arista (Universitas Muria Kudus, 2023)
The purpose of this research is to describe the factors that cause a lack of reading literacy at MTs Sabilul Ulum Mayong and help students become better reading literacy through behavioristic counseling using the behavior contract technique. The type of research used is case study research. The subjects of this study were students at MTs Sabilul Ulum Mayong who lacked literacy, including only being absent during online learning, being late in submitting assignments, not paying attention to the teacher during lessons, and so on. The data analysis used is inductive qualitative data analysis consisting of data reduction, presentation and conclusion. The results showed that the students of MTs Sabilul Ulum Mayong experienced an increase in their reading ability after receiving behavioral instructions using the behavioral contract technique.This can be seen from the behavior of the two counselees who are starting to be able to take part in online learning well, submit assignments on time, and pay attention to the teacher during learning. Thus it can be concluded that the lack of reading literacy in MTs Sabilul Ulum Mayong students can be improved through behavioristic counseling with the behavior contract technique